The impact of information technologies and artificial intelligence on economic growth: An analysis of theoretical approaches - Елизавета Мартьянова; Андрей Полбин (Вестник Пермского университета: Серия Экономика)
Introduction. This survey analyzes the impact of information technologies (IT) and artificial intelligence (AI) on economic growth. Despite the clear potential of new technologies, since the mid-2000s, the developed countries have been experiencing both a slowdown in their economic growth rates and a rise in their research and development expenditures. Additionally, market dynamism has been declining, which results in lower firm entry and exit rates, alongside a decrease in labour mobility. Purpose. The article aims at analyzing current studies that explore the lack of notable macroeconomic effects from IT and AI proliferation. Materials and Methods. The study includes critical analysis and discussion of academic literature focused on the macroeconomic effects of IT and AI. Results. A literature review revealed that current studies offer several reasons for no macroeconomic effects from IT and AI proliferation. Some studies suggest that the growth of market power and reduced dynamism are linked to diminishing opportunities for firms to catch up with the leaders due to IT and AI characteristics, such as slower knowledge diffusion and higher importance of intangible assets. Other potential reasons for the lack of IT and AI impacts on economic growth include: a) overly optimistic expectations regarding the productivity effects of IT and AI, b) inaccuracies in measuring the IT and AI effects, c) the use of new technologies for redistributing existing rents rather than creating new added value, and d) implementation and restructuring lags for additional investments and time to integrate general-purpose technologies like IT and AI. Conclusions. Findings from current theoretical models suggest that slowing market dynamism and increasing market power may be linked to IT diffusion. Therefore, the paper may be useful for researchers and economists interested in the factors of economic growth in the context of digital transformation. The conclusion explores potential AI applications to stimulate economic growth.